From Criminal Law to Customary Law: Incest as a Sexual Crime - Hijriani Hijriani; Rizki Ramadani (Yuridika, 2022)
This study analyses several aspects of incest as a sexual crime, as well as its law enforcement, by comparing criminal law and Bugis customary law. This normative study was conducted by examining primary and secondary legal materials, which were then analysed qualitatively and descriptively. The findings indicate that incest can occur in the form of sexual violence caused by internal and external factors, such as psychological and family condition. Incest also has a very serious impact on victims, especially children. In terms of criminal law, the regulation of incest is spread across several laws such as obscenity in Criminal Code (KUHP); sexual intercourse with children in the Child Protection Law; and sexual violence against a family member in the PKDRT Law. However, in the Bugis customary law, incest is a sexual deviation against dignity and honour (siri’). On that basis, incest is determined as the most severe customary offense (malaweng) and is punishable by the death penalty. In principle, the criminal law and Bugis customary law both consider incest a prohibited sexual deviation. Although there are differences regarding the severity of sanctions against perpetrators, both legal routes have proven to be complementary and can be applied in court.